MODERN APPROACHES TO THE USE OF UTEROTONIC DRUGS FOR THE PREVENTION AND TREATMENT OF POSTPARTUM BLEEDING - Артымук, Наталья Владимировна; Марочко, Татьяна Юрьевна; Артымук, Дмитрий Анатольевич; Тачкова, Ольга Анатольевна (Mother and Baby in Kuzbass, 2023)
The aim of the study was to analyze modern approaches to the use of uterotonic drugs for the prevention and treatment of postpartum hemorrhage.Materials and methods: The information databases of the PubMed, MEDLINE, e-library systems were evaluated. Key words (search words): «uterotonic drugs», «uterotonics», «uterotonic therapy». The search depth was 3 years (2020-2023).Results. As a result of the search, 138 publications were found, 38 publications corresponded to the search criteria. One of the main methods of management of hypotonic postpartum hemorrhage is uterotonic therapy, either as monotherapy or in combination with other methods, such as compression suture and/or controlled balloon tamponade. Oxytocin and carbetocin are generally recognized as first-line uterotonics, and ergot alkaloids and prostaglandins are generally recognized as second-line uterotonics. The high efficacy and safety of terlipressin in high-risk patients with delivery by caesarean section has been proven.Conclusions. Further multicenter studies are needed to determine the minimum effective dose of uterotonics in low-risk patients and the possibility of combining different uterotonics in high-risk patients.
Keywords: postpartum hemorrhage; uterotonics; uterotonic therapy; oxytocin; ergot alkaloids; prostaglandins; terlipressin